POLITENESS STRATEGY USED BY STUDENTS AT SANTHI BUDAYA ART FOUNDATION STUDIO AND CULTURE - ., Komang Savitri Putri; ., Drs.Gede Batan,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Universitas Pendidikan Ganesha, 2017)
This study aimed to analyze the politeness strategies used by students of Santhi Budaya Art Foundation Studio and Culture in communicating and interacting with their coaches and the reasons students use these politeness strategies to communicate with their coaches to achieve their communication goals. This is a descriptive study and the instrument used to collect data were the researcher, observation check-list, interview guide, and phone mobile recorder. The result of the study showed that 1) there were 4 types of politeness strategies used by the students to communicate with their coaches. These strategies were: bald record, positive politeness, negative politeness and off record in which the bald record strategy was more dominantly used 2) the first reason for using politeness strategy when communicating with the coaches was because students needed to respect someone older than them and the second reason was because students needed to respect someones who had a higher status than them.Kata Kunci : Politeness strategy, Coach, Students This study aimed to analyze the politeness strategies used by students of Santhi Budaya Art Foundation Studio and Culture in communicating and interacting with their coaches and the reasons students use these politeness strategies to communicate with their coaches to achieve their communication goals. This is a descriptive study and the instrument used to collect data were the researcher, observation check-list, interview guide, and phone mobile recorder. The result of the study showed that 1) there were 4 types of politeness strategies used by the students to communicate with their coaches. These strategies were: bald record, positive politeness, negative politeness and off record in which the bald record strategy was more dominantly used 2) the first reason for using politeness strategy when communicating with the coaches was because students needed to respect someone older than them and the second reason was because students needed to respect someones who had a higher status than them.keyword : Politeness strategy, Coach, Students